2008
DOI: 10.1016/j.jtcvs.2008.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activity and aspirin efficacy after off-pump compared with on-pump coronary artery bypass surgery: Results from the prospective randomized trial PRAGUE 11–Coronary Artery Bypass and REactivity of Thrombocytes (CABARET)

Abstract: The platelet activity is higher in the early postoperative period in off-pump compared with on-pump coronary artery bypass grafting. The present aspirin strategy seems to be insufficient in the early postoperative period, irrespective of the surgical technique used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 30 publications
(35 reference statements)
0
10
0
1
Order By: Relevance
“…Using flow cytometry, Bednar et al [16] detected a 53% increment of CD62P expression at 48 h postoperative in patients who underwent OPCAB after preoperative aspirin discontinuation, compared with those who underwent on-pump CABG after preoperative aspirin discontinuation. This findings suggests that platelet activation during the early postoperative period could be more serious during OPCAB than during on-pump CABG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using flow cytometry, Bednar et al [16] detected a 53% increment of CD62P expression at 48 h postoperative in patients who underwent OPCAB after preoperative aspirin discontinuation, compared with those who underwent on-pump CABG after preoperative aspirin discontinuation. This findings suggests that platelet activation during the early postoperative period could be more serious during OPCAB than during on-pump CABG.…”
Section: Discussionmentioning
confidence: 99%
“…Bednar et al presented 53% increment of CD62P expression at postoperative 48 hours in patients who stopped administration of preoperative aspirin in OPCAB [16]. We used these data to find out sample size for our study.…”
Section: Methodsmentioning
confidence: 99%
“…Several reports have documented the existence of a relative hypercoagulable state after off-pump surgery, associated with higher levels of postoperative platelet activity and a decrease in platelet sensitivity to aspirin after OPCAB. [52][53][54][55][56][57][58][59][60] Moreover, in some early studies of graft patency after OPCAB, vein graft occlusion was noticeably higher both early and late after OPCAB compared with conventional CABG. 53,61 Questions were therefore raised about whether antiplatelet therapy with aspirin alone would be sufficient for patients after OPCAB, and as early as 2003, leading off-pump centers instituted policy changes to treat all OPCAB patients with both clopidogrel and aspirin after surgery for a duration of 3 months.…”
Section: Off-pump Cabgmentioning
confidence: 99%
“…19,20 Furthermore, clopidogrel may work to prevent atherothrombotic events more effectively in off-pump CABG compared with on-pump CABG because of differences in platelet function early after surgery. 21,22 The CASCADE randomized trial showed that there was no difference in SVG patency or the volume of SVG intimal hyperplasia between aspirin-clopidogrel and aspirin-placebo groups. 6 However, most operations were performed on-pump in the CASCADE trial (96%), and, as a corollary, it is conceivable that the effects of clopidogrel on native CAD progression could be more pronounced with off-pump CABG than what the present study showed.…”
Section: September 9 2014mentioning
confidence: 99%